2016
DOI: 10.1007/s00127-016-1173-z
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood settings, types of social capital and depression among immigrants in Toronto

Abstract: Results suggest that social cohesion might have a protective effect from depression among immigrants in NEHW. In IRN, lower linking social capital associated with lower depression might reflect opposite direction association. Bridging social capital was not associated with depression in either sample, indicating that current community building might be insufficient to impact depression. Different pathways might explain how depression among immigrants is impacted by social capital types operating in different n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
3
18
0
1
Order By: Relevance
“…For associations between bonding social capital and depressive state at the baseline, which corresponded to the contemporaneous association between bonding social capital and depression, we confirmed that bonding types of social capital at the baseline (intercepts) were negatively associated with depressive state at the baseline for both men and women. These results support previous findings [ 15 , 16 , 29 ]. Bonding social capital refers to aspects of “inward-looking” social networks that reinforce homogeneous groups [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For associations between bonding social capital and depressive state at the baseline, which corresponded to the contemporaneous association between bonding social capital and depression, we confirmed that bonding types of social capital at the baseline (intercepts) were negatively associated with depressive state at the baseline for both men and women. These results support previous findings [ 15 , 16 , 29 ]. Bonding social capital refers to aspects of “inward-looking” social networks that reinforce homogeneous groups [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, bridging social capital at the baseline was not associated with depressive state at the baseline for either men or women, as has been described in previous studies [ 16 , 29 ]. Bridging social capital refers to “outward-looking” social networks with different members that do not necessarily share similar identities [ 21 ].…”
Section: Discussionsupporting
confidence: 76%
“…For historical reasons, 85% of Arabs live apart from the Jews; there are only eight mixed towns in Israel. Despite the health benefits of the 'ethnic density effect' (Becares et al 2009), which suggests a protective effect for minorities living in concentrated areas, neighbourhood segregation is fundamental to discrimination and a root cause of racial and socioeconomic inequalities in health (Daoud et al 2016;Daoud et al 2017;Williams and Collins 2001). Likewise, ward economic deprivation in the UK has been associated with poorer health among Pakistani, Bangladeshi and other minorities (Chandola 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this approach, higher exposure to stress and higher vulnerability among minorities adversely affect health (Krieger et al 2011), both through biological, neuro-psychological mechanisms, and indirectly through risky behaviours like smoking (Mindell et al 2014). Other approaches relate to the social and structural living environment, emphasizing the role of neighbourhood SES, community social cohesion (Daoud et al 2016) and social capital (Daoud et al 2017;Kawachi et al 1999) in explaining health inequalities, although the role of social capital remains controversial (Uphoff et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although neighborhood is a major social determinant of mental health [ 78 , 79 , 80 , 81 , 82 , 83 ], a growing body of evidence has documented heterogeneity of the neighborhood-health link based on race, ethnicity, and gender [ 12 , 17 , 20 ]. Using a local sample of Black youth, a recent longitudinal study showed similar results.…”
Section: Discussionmentioning
confidence: 99%